Perceptions on environmental issues related to forest in Cameron Highlands, Pahang - Suhadak, Ummu Afina Ufiya (2019)
Forest is one of the essential ecosystems that give many benefits to humanity and all living organism by providing food, shelter, medicinal plants and environmental protection. The objectives of the study were to investigate the issue of forest exploitation in Cameron Highlands and examine perception on appropriate conservation measures that can be used to protect forests in Cameron Highlands. The convenience sampling was used on the data collected from population members who are conveniently available to participate in the study. Face to face interviews using a structured questionnaire were conducted on 110 conveniently and randomly selected respondents who were tourists and the local community in Cameron Highlands. The study revealed that 52.7% of respondents think that the most forest exploitation issue that occurs in Cameron Highlands was forest conversion into agriculture. This study also shows that some respondent‟s characteristics have a significant correlation with the respondent‟s perception towards forest protection in Cameron Highlands. From the result, it shows that not all socio-demographic characteristic influence their perceptions.